Aransemen Lagu Buku Ende No.171 “Tandai Ma Au” Karya William Howard Doane Dalam Instrument Saxophone Dan Biola - Waldes Christopel Manalu; Lince Rauli Ture Simamora; Roy Joseph (Universitas Katolik Widya Karya Malang, 2023)
This thesis discusses the arrangement of the song Tanda I Ma Au Buku Ende Number 171 for saxophone and violin instruments. This arrangement was worked on by the author by collaborating on a trio of saxophone, trombone and violin into one complete piece as a new composition and can be played in worship at HKBP Simanungkalit. The aim of this research is to find out the results of the collaboration on the arrangement of saxophone and violin instruments in the song Tanda I Ma Au. In presenting this arrangement the author made a change from the original tempo of 70 to a tempo of 60, namely in bar 14 or the second verse, which aims to give a grand impression and a deeper soul to the song. This research uses descriptive analysis methods with a qualitative approach. The work processes carried out are observation, documentation and recording of activities. The research results show that the song Tanda I Ma Au Buku Ende Number 171 is very dominant when accompanied by saxophone and violin which was arranged by the author.